Microstructure and Performance of Body-Centered Cubic-Based Dual-Phase Composite Eutectic High-Entropy Alloys Prepared by Si Doping - Saike Liu; Aoxiang Li; Kaiwen Kang; Jinshan Zhang; Di Huang; Chunning Che; Yiteng Jiang; Mingkun Xu; Borui Zhang; Yaqing Li; Gong Li (Metals)
AlCrFeNi-based high-entropy alloys (HEAs) have emerged as a prominent research system, attracting significant interest due to their compositional diversity and the tunability of their phase structures. However, in practical applications, single-phase AlCrFeNi-based HEAs often face a trade-off between toughness and strength. Therefore, designing multi-phase composite eutectic high-entropy alloys (EHEAs) to optimize their mechanical properties and microstructure has become a key research focus. Si, a common non-metallic element, plays a significant role in strengthening metal materials. In this paper, AlCrFeNi with Si doping strengthening (AlCrFeNi)100-xSix composite EHEAs were successfully fabricated. A systematic analysis was conducted to investigate the impacts of Si doping on the microstructure and mechanical properties of AlCrFeNi-based composite EHEAs. This study shows that with increasing Si content, the biphasic lamellar composite structure at the grain boundaries gradually expands, forming flower petals. The precipitate structure within the grains evolves into flower disks, which form a sunflower-like composite structure in the alloy. The volume fraction of lamellar structures increases in the petals, accompanied by grain refinement. Furthermore, the yield strength of the alloy increases from 1131 MPa to 1360 MPa with increasing Si content. This provides guidance for the design of high-performance composite EHEAs.